Similar outcome of heart failure with reduced EF patients with and without atrial fibrillation: considerations from the ESC Heart Failure Long-Term Registry - De Vecchis, Renato (Monaldi Archives for Chest Disease, 2019)
Recently, transcatheter ablation of atrial fibrillation (AF) has been validated by international societal guidelines as a technique suitable for both treatment and secondary prevention of paroxysmal, persistent or long-lasting persistent AF in highly symptomatic patients in whom at least one antiarrhythmic drug had been tested.